Do Citizens Perceive Elected Politicians, Experts and Citizens as Alternative or Complementary Policy-Makers? A Study of Belgian Citizens - Pilet, Jean-Benoit; Talukder, David; Sanhueza, Maria Jimena; Rangoni, Sacha (Frontiers in Political Science, 2020)
In the scholarly literature, studies have underlined a link between citizens' low levels of support for elected politicians and demands for a greater role of other actors such as citizens themselves or independent experts in policy-making. Yet, what remains unclear is whether such demands to increase the role of these actors are rooted in a desire to replace entirely politicians, or whether citizens and experts are perceived as complementary to elected politicians. It is precisely what we explore in this article. Using data from 2019 Belgian Election survey, we conduct a latent profile analysis to see what models of governance emerge among citizens. First, we demonstrate that while some citizens indeed perceive politicians, citizens and experts as separate governing groups, others combine support for multiple actors. Building on the typologies that emerge, we conduct two complementary analyses. In the second section, we try to analyse how these different views regarding who should govern translate into support for specific institutional reforms consultative referenda, binding referenda, assemblies of citizens and a government of experts. Our results show that, in general, citizens tend to favour the mechanisms that empower the actors they support, for instance deliberative democracy mechanisms are preferred by those who are positive about citizens as policy-makers. Finally, in the last section we examine the impact of citizens’ personal characteristics (age, gender, education, employment) and political attitudes (political interest, political knowledge, political trust, left-right) on belonging to each of the latent classes identified. We determine the main socio-demographic traits and/or political attitudes that predict the likelihood of belonging to one of the seven classes. For example, we observe that people who delegate decision-making to politicians and experts share better socio-economic conditions and have higher levels of political interest and political knowledge. We close our analysis by explaining the importance of taking into account such preferences for a mix of policy-makers (citizens, experts and politicians) in broader debates on models of democracy.